2021
DOI: 10.1111/aas.13991
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Evaluation of Coronavirus Illness Severity (RECOILS) in intensive care: Development and validation of a prognostic tool for in‐hospital mortality

Abstract: Background The prediction of in‐hospital mortality for ICU patients with COVID‐19 is fundamental to treatment and resource allocation. The main purpose was to develop an easily implemented score for such prediction. Methods This was an observational, multicenter, development, and validation study on a national critical care dataset of COVID‐19 patients. A systematic literature review was performed to determine variables possibly important for COVID‐19 mortality predicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…However, many studies showed high risk of bias [1] and only few temporally validate the models [27] , [28] , [29] . Our performance in the temporal validation is in line with another externally-validated model developed on EHR data [30] , as well as other studies that take into account readily availability data [31] , [32] . The importance of external validation and continuous monitoring and updated of machine-learning models to ensure their long-term safety and effectiveness has also been underlined by previous studies [33] , [34] .…”
Section: Discussionsupporting
confidence: 84%
“…However, many studies showed high risk of bias [1] and only few temporally validate the models [27] , [28] , [29] . Our performance in the temporal validation is in line with another externally-validated model developed on EHR data [30] , as well as other studies that take into account readily availability data [31] , [32] . The importance of external validation and continuous monitoring and updated of machine-learning models to ensure their long-term safety and effectiveness has also been underlined by previous studies [33] , [34] .…”
Section: Discussionsupporting
confidence: 84%
“…To compare the ISARIC 4C mortality score and the CURB-65 score, the ISARIC-4C score was standardized into three risk groups (low [0–3], medium [ [4] , [5] , [6] , [7] , [8] ], and high [ 9 , 21 ]) to avoid a different number of risk groups between both scores according to the guidelines [ 18 , 19 ]. The diagnostic accuracy of both scores was evaluated by calculating sensitivities, specificities, positive predictive value, negative predictive value, and Youden's J indices (YJI) [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, early identification of subgroups at increased risk of deterioration and needing ventilation or critical care is essential for more effective medical care. Appropriate and rational patient triage strategies improve the decision-making process related to resource allocation, including hospital bed occupancy, critical care resource consumption, and preservation of the most needful and expensive therapy options for critically ill patients [ [3] , [4] , [5] ].…”
Section: Introductionmentioning
confidence: 99%
“…In patients with COVID-19-associated ARF, the PaO 2 /FiO 2 ratio was able to predict severity in a cohort of 421 patients [ 26 ], as well as in a smaller cohort of 150 patients. In the latter cohort, the authors were able to calculate an optimal cut-off PaO 2 /FiO 2 ratio of 274 mmHg, which could distinguish between patients with mild disease and patients with severe disease with a sensitivity of 72% and specificity 85% [ 27 ], and it also contributed to a predictive composite score along with age, platelets, pH, blood urea nitrogen, temperature, PaCO 2 , and Glasgow Coma Scale in a cohort of 937 patients [ 28 ].…”
Section: Diagnosing Acute Respiratory Failurementioning
confidence: 99%